2008
DOI: 10.1007/s11121-008-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarette Price Increases on Smoking Cessation in California

Abstract: We investigated whether smoking cessation increased in California after a cigarette manufacturer's retail price increase and an increase in the state cigarette excise tax. The sample for this study was drawn from the 1996 and 1999 California Tobacco Surveys. The rate of unsuccessful and successful quit attempts and the rate of abstinence were calculated for each month of the 14-month period preceding each survey administration. We combined the monthly rates for both surveys and used multiple regression modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…Consistent with the health economics studies,5 6 we found a clear and robust relationship between price and cessation motivation. Moreover, this study extended the literature with several new findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the health economics studies,5 6 we found a clear and robust relationship between price and cessation motivation. Moreover, this study extended the literature with several new findings.…”
Section: Discussionsupporting
confidence: 89%
“…One of the major factors in smoking cessation is the price of cigarettes 4. For example, tax increases have been shown to significantly increase quit attempts 5 6. To date, however, most of the studies on the relationship between cigarette price and smoking cessation are from the domain of applied microeconomics.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors seemed important in decreasing tobacco use in the United States population. Taxation helped reduce the use of tobacco, but the largest decrease in tobacco use came immediately following tax increases (24), similar to decreased consumption noted following sharp price increases in Russia. However, tobacco control programs were also useful in decreasing tobacco use (25).…”
Section: Discussionmentioning
confidence: 84%
“…Taxation, media, and government restrictions on smoking in public settings have been associated with greater quit rates, lower initiation rates, and decreasing prevalence rates of smoking (Glantz, 1993;Goldman & Glantz, 1998;Levy, Mumford, & Gerlowski, 2007;Levy, Romano, & Mumford, 2005;Reed, Anderson, Vaughn, & Burns, 2008). These findings suggest that the most powerful means of reducing prevalence of smokers is culture change that includes policy regulations that increase costs and decrease smoking in public and private microenvironments.…”
Section: Discussionmentioning
confidence: 94%